The influence of tax burden, intangible assets, and foreign ownership on transfer pricing policies - Pratiwi, Nur Aisah Eka; Wadi, Indra (Educoretax, 2024)
This research aims to determine and empirically test the influence of tax burden, intangible assets and foreign ownership on transfer pricing policies in energy sector companies listed on the Indonesia Stock Exchange (BEI) during the 2018 2022 period. This type of research is descriptive quantitative which uses secondary data sourced from the company's financial reports that have been published by the company on the Indonesia Stock Exchange (BEI). This research consisted of 84 companies and the number of samples used was 9 companies as research objects for five years. The data analysis technique for testing this hypothesis uses E-views 12 software. Panel data regression analysis is used as the mechanism in this research. The research results show that the tax burden has a significant effect on transfer pricing. Meanwhile, intangible assets and foreign ownership do not have a significant effect on transfer pricing. This is because companies can consider tax burdens, intangible assets and foreign ownership in transfer pricing policies